A RADIOGRAPHY OF THE VALUE REGISTER OF FUTURE TEACHER STUDENTS - Vali ILIE; Ecaterina Sarah FRĂSINEANU (Universitaria Publishing House, Craiova, 2024)
Students are perceived as a group that manifests certain specific cultural particularities, among which there are the values, beliefs and principles of conduct. Since the instructional-educational activities carried out with them must take into account those aspects that they value and which represent benchmarks in the cognitive, affective and behavioral spheres, we decided to find out which axiological benchmarks the students we work with refer to. They assimilate the cultural values promoted by the university and, at the same time, they are active participants in the act of creating new values. We were interested in identifying the most common values among master's students who are enrolled in the courses of the psychopedagogical module and also to what extent these are found in their attitudes and opinions in specific training situations. In order to achieve the proposed goal, we started from the hypothesis that students refer to both classical and recent values. In order to test the research hypothesis, we used qualitative research methods, which allowed us to inventory the dominant values of the students' axiological register, but also to find out some reasons and arguments they base their opinions on.